Hydrogen Sulfide Regulates Energy Production to Delay Leaf Senescence Induced by Drought Stress in Arabidopsis - Jin, Zhuping; Sun, Limin; Yang, Guangdong; Pei, Yanxi (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S) is a novel gasotransmitter in both mammals and plants. H2S plays important roles in various plant developmental processes and stress responses. Leaf senescence is the last developmental stage and is a sequential degradation process that eventually leads to leaf death. A mutation of the H2S-producing enzyme-encoding gene L-cysteine desulfhydrase1 (DES1) leads to premature leaf senescence but the underlying mechanisms are not clear. In this present study, wild-type, DES1 defective mutant (des1) and over-expression (OE-DES1) Arabidopsis plants were used to investigate the underlying mechanism of H2S signaling in energy production and leaf senescence under drought stress. The des1 mutant was more sensitive to drought stress and displayed accelerated leaf senescence, while the leaves of OE-DES1 contained adequate chlorophyll levels, accompanied by significantly increased drought resistance. Under drought stress, the expression levels of ATPβ-1, -2 and -3 were significantly downregulated in des1 and significantly upregulated in OE-DES1, and ATP showed the opposite trend. Senescence-associated gene (SAG) 12 correlated with age-dependent senescence and participated in the drought resistance of OE-DES1. SAG13, which was induced by environmental factors, responded positively to drought stress in des1 plants, while there was no significant difference in the SAG29 expression between des1 and OE-DES1. Using transmission electron microscopy, the mitochondria of des1 were severely damaged and bubbled in older leaves, while OE-DES1 had complete mitochondrial structures and a homogeneous matrix. Additionally, mitochondria isolated from OE-DES1 increased the H2S production rate, H2S content and ATPase activity level, as well as reduced swelling and lowered the ATP content in contrast with wild-type and des1 significantly. Therefore, at subcellular levels, H2S appeared to determine the ability of mitochondria to regulate energy production and protect against cellular aging, which subsequently delayed leaf senescence under drought-stress conditions in plants.